Operating parameters of liquid helium transfer lines used with continuous flow cryostats at low sample temperatures. Issue 1 (November 2015) - Dittmar, N; Welker, D; Haberstroh, Ch; Hesse, U; Krzyzowski, M
Abstract: Continuous flow cryostats are used to cool samples to a variable temperature level by evaporating a cryogen, e.g. liquid helium (LHe). For this purpose LHe is usually stored outside the cryostat in a mobile dewar and supplied through a transfer line. In general, the complete setup has to be characterised by the lowest possible consumption of LHe. Additionally, a minimum sample temperature can be favourable from an experimental point of view. The achievement of both requirements is determined by the respective cryostat design as well as by the transfer line. In the presented work operating data, e.g. the LHe consumption during cooldown and steady state, the minimum sample temperature, and the outlet quality are analysed to characterise the performance of a reference transfer line. In addition, an experimental transfer line with built-in pressure sensors has been commissioned to examine the pressure drop along the transfer line, too. During the tests LHe impurities occurred which restricted a steady operation.